Father-child attachment among 5-6 year olds: A Survey Study - Randiawan, Randiawan; Muthmainah, Muthmainah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The bond between fathers and children is essential for emotional and social development, especially in early childhood. This study aims to explore the level of attachment between fathers and their children aged 5–6 years in Parigi. A quantitative approach with a descriptive survey method was employed. Data were collected using a questionnaire based on the Inventory of Parent and Peer Attachment (IPPA) theory, which includes dimensions of communication, trust, and alienation. The sample consisted of 172 father-child pairs from 13 kindergartens, although only 172 responses were analyzed. Results showed an average attachment score of 71.02 (SD = 5.81), with scores ranging from 60.50 to 82.30. Most relationships were categorized as medium attachment (45%) and were classified in the moderate attachment category, particularly within the score range of 62.51 to 71.6. Notably, none of the participants fell into the very high attachment category (?83.72), indicating potential areas for strengthening emotional bonds. These findings underscore the need for targeted interventions, such as parenting policies, school-based father involvement programs, and community-based mentoring initiatives aimed at enhancing fathers’ emotional engagement and responsive caregiving.